Comparing vaccination coverage and dog population demographics among four pilot dog rabies vaccination strategies in Uganda - Akankwatsa, Dickson; Odoch, Terence; Kahunde, Anna Mary; Hartnack, Sonja; Bagonza, Arthur; Kiguli, Juliet; Okech, Samuel George; Herrera, Adrian; Kankya, Clovice; Mohammed, Lamorde; Agado, Doreen; Léchenne, Monique; et al. (Frontiers in Veterinary Science, 2025)
IntroductionThe zero by 30 initiative aims to eliminate dog-mediated human rabies by 2030, for which dog vaccination is a crucial pillar. This study piloted four different dog vaccination campaign strategies in Kyegegwa, a rural district in Uganda, where rabies is endemic, and compared the vaccination coverages achieved by the strategies.MethodsFour vaccination strategies were rolled out, each in three parishes from different sub-counties: (i) static point vaccination (SP), (ii) school-based (SB, i.e., information campaigns were mainly conducted at schools and vaccination was done at the school during weekends), (iii) integrated dog with livestock vaccination (D-L), and (iv) integrated dog vaccination with human health services (D-H, One Health approach). Vaccination coverage was estimated using transect and household survey data, analyzed with a Bayesian model that estimated, besides the vaccination coverage, the dog population size and the proportion of ownerless dogs for each dog population.ResultsThe mean vaccination coverage achieved among the owned dog population across the three parishes for each respective strategy was 29.5% for SP strategy (the model converged in one parish only), 53.9% (range 27.4–79.5%) for SB, 66.2% (range 53.5 and 86.0%) for the D-L, and 74.5% (range 63.7 and 88.4%) for D-H. The mean proportion of ownerless dogs in the villages investigated was estimated at 0.1% for the parishes with SP strategy, 7.0% (range 0.1–20.8%) for SB strategy, 29.7% (range 0.5–88.1%) for D-L, and 7.9% (range 0.3–17.7%) for D-H strategy villages.DiscussionThe strategy integrating dog vaccination with human health services outperformed the other strategies by achieving the highest mean vaccination coverage and reaching a constantly high coverage of above 60% for all the three parishes of that strategy. This demonstrates the potential of the human-animal integrated D-H vaccination strategy as an effective approach for rabies control. Sensitization strategies for dog owners also depended in the vaccination strategy performed, i.e., spread of information through health centers for the D-H strategy, which is part of the success of this strategy. The study needs to be taken as a pilot, because of limitations such as different settings between the sub-counties. Further testing across diverse settings can help assess integrated dog vaccination strategies’ consistency and scalability, providing valuable insights for developing a One Health model to strengthen future rabies elimination efforts.